Feed Enrichment with Amylolytic Lactic Acid Bacteria to Stimulate the Growth of Freshwater Crayfish (Cherax quadricarinatus) - Dahlia, Dahlia; Hasniar, Hasniar; Seniati, Seniati; Ardiansyah, Ardiansyah; Idris, Andi Puspa Sari; Hartinah, Hartinah (Aquacultura Indonesiana, 2018)
The goal of feed enrichment with amylolytic Lactic Acid Bacteria (LAB) was to get an optimal feed formula in stimulating the growth of freshwater crayfish (Cherax quadricarinatus). The research design used a completely randomized block design, which consists of 2 groups (Group I = probiotic HS7 with inoculum density 108 and Group II = probiotic HS7 with density 1010). Each group were given 4 different treatment (Feed A = protein 50%-carbohydrate 20%; Feed B= protein 40%-carbohydrate 30%; Feed C= protein 30%-carbohydrate 40%; and Feed D= protein 20%-carbohydrate 50%), with 2 repetition. The parameter observed in this study was daily growth rate and absolute growth. The result showed that Feed C, composed by protein 30%-carbohydrate 40% with LAB enrichment and inoculum density of 108  gives the best growth, with daily growth rate of ± 0.22-0.23 % each day and absolute growth of ± 13.10-13.20 gram in 75 days.